Evaluation of comparability of results of determination of phenol in the immune-biological medicines - O. N. Kolesnikova; M. G. Korotkov; V. I. Malkova; O. B. Runova; O. B. Ustinnikova; V. I. Klimov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The article presents the practical assessment of the possibility of harmonization and standardization of methods for the determination of phenol in the immunebiological medicines. The evaluation of the statistical significance of differences in the results of determinations of phenol existing methods described in the standard documentation for foreign and domestic preparations: used ANOVA with Fisher’s exact test (F-test). The conclusion of the interchangeability of the studied methods for the determination of phenol in the immune-biological medicines and the opportunity of the development and certification of standard reference and sample validation measurements.